THE RELATIONSHIP BETWEEN BREASTFEEDING FREQUENCY AND PHYSIOLOGICAL JAUNDICE IN NEONATES AT THE TAMPOJUNG PREGI WARU PAMEKASAN PUBLIC HEALTH CENTER - Rohemah (Jurnal Medicare, 2026)
Physiological jaundice is a common condition in neonates, typically appearing on the second to fifth day of life and resolving within 1–2 weeks. One factor influencing the occurrence of physiological jaundice is the frequency of breastfeeding. Adequate breast milk intake helps accelerate the elimination of bilirubin through feces and urine. The purpose of this study was to determine the relationship between breastfeeding frequency and the incidence of physiological jaundice in neonates. The research design used was analytical with a cross-sectional approach. The population and sample in this study were infants born at term at the Tampojung Pregi Community Health Center within 1 month with a sample size of 25 respondents. Sampling in this study used the Probability Sampling technique. Data collection used a questionnaire that was processed using the Chi-square test. Based on the Chi Square statistical test with the help of SPSS software, the significance (p) was 0.012 and α 0.05, so p was obtained which was smaller than α 0.000 < 0.05, so Ho was rejected and H1 was accepted. So there is a relationship between breastfeeding frequency and physiological jaundice in neonates.